Produção de etanol e hidrolisado protéico da casca de soja - Rojas, Mayerlenis Jiménez (2012)
Soybean hull is a lignocellulosic biomass that contains 38-51% of cellulose, which could be converted to ethanol. In addition, contains 9-14% of protein that can be hydrolyzed by endoproteases, releasing oligopeptides with nutritional applications. Although glycoside and peptide linkages can be hydrolyzed by acids, the cellulose molecules are more resistant than the protein and hemicellulose molecules. In this way, the acid treatment of the biomass would reduce its hemicellulose content, and the remnant cellulose into solid fraction would be more susceptible to hydrolytic enzymes. In this work, different routes of protein, hemicellulose, and lignin solubilization were evaluated, intending to obtain ethanol and soluble oligopeptides from the soybean hull. The protein was recovered as oligopeptides by hydrolysis of the lignocellulosic biomass using the commercial endoprotease Novo-Pro DR at 60oC, pH 9.0, 5 h, and different enzyme concentrations (1, 2, and 4%, m/m). A sequential hydrolysis using chymotrypsin and Novo-Pro DR, both at 1% (m/m) enzyme concentration, was also evaluated. The results showed that hydrolysis with 1% Novo-Pro DR allowed solubilization of 56.9% of protein from the soybean hulls. Nonetheless, at same temperature and pH, in absence of enzyme, was possible to solubilized 45.6% of the proteins. This solubilization is probably due to liberation of the physically aggregated units. The increase of endoprotease concentration from 1 to 2% increased the protein removal to 74%. However, the increase from 2 to 4% not increased significantly the protein solubilization. The use of chymotrypsin, an enzyme with high specificity and that work at mild conditions, allowed a solubilization of 44% protein. Nonetheless, the removal of lignin using chymotrypsin was higher than that using Novo-Pro DR. When in-nature soybean hull was hydrolyzed by acid or protease (1% Novo-Pro DR) followed by acid, the protein removal was around of 90%. The lignocellulosic biomass was hydrolyzed with 3% (v/v) H2SO4, solid:liquid ratio of 1:4, 120oC, and 20 min. 20 min. Carbohydrate analyses showed that the acid treatment allowed to hemicellulose removal around of 46.7% in the xylose form. The protein content of the soybean hull was almost totally solubilized during the acid hydrolysis, without significant loss of cellulose. On the contrary, large cellulose loss was observed during the acid hydrolysis of in-nature soybean hull. In this way, if it is intended to produce a protein hydrolysate containing controlled composition or ethanol from remnant solid fraction, is strongly recommended the previous enzymatic solubilization of the proteins. The chemical composition of the solid biomass after sequential hydrolyses with protease and acid showed cellulose content around of 49% for all samples. So, the biomass treated with 1% (m/m) Novo-Pro DR was saccharified with Acellerase 1500 at 50oC, pH 4.8, and enzyme/substrate ratio of 7 FPU/g of cellulose for 72 h. Under the same conditions, soybean hull in-nature, pretreated with acid, and pretreated with protease were submitted to cellulolytic hydrolyses. The cellulose-to-glucose conversion was around of 40% for the last two biomass. The increase of the enzymatic load to 20 FPU/g of cellulose allowed a cellulose conversion of 55% for biomass pretreated with 1% (m/m) Novo-Pro DR, followed by acid hydrolysis. The supplementation of the Acellarase 1500 with 120 IU of β-glucosidase and 1% (m/m) of pectinase not produced any increased in the cellulose conversion. The biomass was pretreated by organossolv method (50% ethanol, 170oC, and 1h) and saccharified with Acellerase 1500 under the same conditions described above. This procedure yielded a cellulose conversion of 52%, with less removal of hemicellulose. This result showed that lignin was causing greater steric hindrances to the enzymatic attack. The biomass pretreated with acid and with protease (1% Novo-Pro D) followed by acid yielded the same glucose-toethanol conversion, reaching an ethanol concentration around of 13 g/L.